Inspirace z Bulharska: Kulturní antropologie a ekonomická migrace, více než jen kamarádky - Gabriela Fatková (Studia Ethnologica Pragensia, 2016)
Several years lasting research of economic migration between Bulgaria and Greece brought a personal transformation in the author’s life, which turned her into a Bulgaria based work migrant. This essay question the possible effects of economic migration of a fieldworker and their methodological consequences. Author also targets the outstandingly frequent involvement of anthropology graduates within the work migration cycles, interestingly these flows aim not only towards “the West” but also “the East”. The stereotype of unqualified economic migrant moving from “East” to “West” flooding the target country with people of their own needs to be reconsidered. Economic migration embrace people with different educational level, and field backgrounds, furthermore some fields like social-cultural anthropology are even more involved. It can challenge anthropology graduates to get the best from this situation, if not for the scientific progress, then at least to self-explain their career choice.